2016
DOI: 10.1155/2016/5685261
|View full text |Cite
|
Sign up to set email alerts
|

The Costs and Their Determinant of Cesarean Section and Vaginal Delivery: An Exploratory Study in Chongqing Municipality, China

Abstract: Objectives. This study aims to analyze the cesarean section (CS) rates and vaginal delivery rates in tertiary hospitals of China, explore the costs of two different deliveries, and examine the relative influencing factors of the costs in both CS and vaginal deliveries. Methods. 30,168 anonymized obstetric medical cases were selected from three sample tertiary hospitals in Chongqing Municipality from 2011 to 2013. Chi-square test was used to compare the distributions of CS and vaginal deliveries under different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
33
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 32 publications
9
33
0
1
Order By: Relevance
“…This is because in mother age over 35 years have a risk of complications in childbirth. This finding is in line with a study by Zhife He et al in China that the proportion of caesarean section delivery in mothers older than 35 years is greater than for normal delivery (He et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…This is because in mother age over 35 years have a risk of complications in childbirth. This finding is in line with a study by Zhife He et al in China that the proportion of caesarean section delivery in mothers older than 35 years is greater than for normal delivery (He et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…1,2 The trend towards an increase in the number of cesarean sections is observed worldwide -except for the Netherlands and other European countries, where it is minor -with Brazil as a leader. 3 Two decades ago, the World Health Organization (WHO) published the report "Safe Motherhood" with recommendations on appropriate obstetric practices and those to be avoided. 4 Evidence based on systematic reviews suggests that ambulating and staying in upright positions during the first period of labor reduces the duration of labor, the risk of cesarean section and the use of analgesia, while not posing risks to the mother or the newborn.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of cesarean delivery (CD) in China [1][2][3][4][5] has risen markedly from 2.0% (14/701) in 1978-1985 to 36.6% (813/2224) during 2006-2010 [1] . In the recent years, nearly half of all newborns in China were delivered by CD [2,3] , among which 23.2% were performed based on maternal request cesarean delivery (MRCD) rather than on medical indications [6] . The high rate of overall CD may result in 3 increased risk of maternal complications such as infection, hemorrhage, or even death [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The high rate of overall CD may result in 3 increased risk of maternal complications such as infection, hemorrhage, or even death [6] . Previous researches have showed that Chinese women choose CD only to avoid the pain during vaginal delivery, because normally no analgesia will be given during their labor and delivery in China [2,7] .…”
Section: Introductionmentioning
confidence: 99%